University Ownership as a Moderator Effect: The Impact of Human Security of Academic ‎Staff on Job Retention - Al-Refai, Amani Mashhoo Al-Refai; Boulesnane, Farida Rachid‎; IbrahimArman, Husam‎; Talafha, Fuad Taha‎; Al-Hawamdeh, Rose Fowler ‎; Alhawamdeh, Ahmed Mohammad‎; Akhorshaideh, Abdel Hakim Oqlah‎; Ahmad, Alaeddin Mohammad Khalaf‎ (Dirasat: Human and Social Sciences, 2025)
Objectives: This paper aims to investigate the impact of the human security of academic staff on job retention at Jordanian universities. Moreover, to examine the moderator effect of university ownership between human security and job retention at Jordanian private and public universities. Methods: A cross-sectional online questionnaire was used to collect the primary data using a sample of (N=356) respondents who are academic staff at Jordanian governmental and private universities. A structural equation modelling (SEM) was designed to test the relationships between the elements of human security of academic staff and job retention at using University Ownership as a Moderator Effect. Results: The results showed that human security has a significant positive effect on job retention. In addition, job satisfaction has a partial moderating effect since there is a direct, significant positive relationship between human security and job retention for academic staff at Jordanian universities. Conclusions: This paper suggests that universities must develop effective human resource strategies to ensure their academic staff feel secure in all aspects (job security, legal security, economic security, research security, personal and moral security).